2017
DOI: 10.3349/ymj.2017.58.3.497
|View full text |Cite
|
Sign up to set email alerts
|

Port-Site Metastases and Chimney Effect of B-Ultrasound-Guided and Laparoscopically-Assisted Hyperthermic Intraperitoneal Perfusion Chemotherapy

Abstract: PurposeCO2 leakage along the trocar (chimney effect) has been proposed to be an important factor underlying port-site metastasis after laparoscopic surgery. This study aimed to test this hypothesis by comparing the incidence of port-site metastasis between B-ultrasound-guided and laparoscopically-assisted hyperthermic intraperitoneal perfusion chemotherapy (HIPPC).Materials and MethodsSixty-two patients with malignant ascites induced by gastrointestinal or ovarian cancer were divided into two groups to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In gasless endoscopic thyroidectomy, a suction device is connected to the suspension retractor for the suction of surgical smoke, thereby affording better air ow in the operating cavity. In the breast approach endoscopic thyroidectomy with CO 2 insu ation, the aggregated PM in surgical smoke at high concentrations is released via the trocar without ltering due to the presence of the stack effect [20], which may result in high-speed jets. Consequently, the level of emission of surgical smoke to the operating room is further increased.…”
Section: Discussionmentioning
confidence: 99%
“…In gasless endoscopic thyroidectomy, a suction device is connected to the suspension retractor for the suction of surgical smoke, thereby affording better air ow in the operating cavity. In the breast approach endoscopic thyroidectomy with CO 2 insu ation, the aggregated PM in surgical smoke at high concentrations is released via the trocar without ltering due to the presence of the stack effect [20], which may result in high-speed jets. Consequently, the level of emission of surgical smoke to the operating room is further increased.…”
Section: Discussionmentioning
confidence: 99%
“…In gasless endoscopic thyroidectomy, a suction device is connected to the suspension retractor for the suction of surgical smoke, thereby affording better airflow in the operating cavity. In the breast approach endoscopic thyroidectomy with CO 2 insufflation, the aggregated PM in surgical smoke at high concentrations is released via the trocar without filtering due to the presence of the stack effect [20], which may result in high-speed jets. Consequently, the level of emission of surgical smoke to the operating room is further increased.…”
Section: Discussionmentioning
confidence: 99%
“…Another important consideration is port-site metastases during laparoscopic surgery. Ba, et al18 reported that the local microenvironment at the trocar site and specimen delivery are more important than the chimney effect. In our study, we used a laparoscopic bag to prevent port-site metastasis.…”
Section: Discussionmentioning
confidence: 99%